Fantasy sport: a systematic review and new research directions. Issue 5 (20th October 2017) - Tacon, Richard; Vainker, Stephen
ABSTRACT: Research questions: Fantasy sport is an increasingly significant social phenomenon. But what do we actually know about participation in fantasy sport? We examined the extant literature to ask: how has fantasy sport participation been conceptualised; what theoretical frameworks and research approaches have been used; what are their strengths and weaknesses; and what further research is needed to improve our understanding? Research methods: We conducted a systematic review of academic journal articles relating to fantasy sport participation. Seventy-one articles met the inclusion criteria and we analysed them on several dimensions. We then conducted a meta-evaluation of the research approaches used in the 71 studies and extended this through critical discussion and analysis of future research possibilities. Results and findings: Fantasy sport participation has been conceptualised in several ways, but most commonly as a form of consumer behaviour. Studies have used various theoretical frameworks and methodologies, but a majority, to date, have employed quantitative, survey-based approaches. These have advantages, enabling researchers to build on each other's work, but also have certain conceptual and methodological limitations. Implications: If we are to understand the social significance of fantasy sport and develop appropriate managerial policies around it, we require a well-developed understanding of fantasy sport participation. This research synthesis highlights the strengths and weaknesses of existing research and offers suggestions for how future researchers can advance knowledge in this area. In particular, the synthesis suggests we need to offer more multi-level, critical analysis.